interview with Reinhard Zimmermann and Jan Peter Schmidt - Rodrigues Junior, Otavio Luiz; Rodas, Sergio (Revista de Direito Civil Contemporâneo, 2015)
interview with Reinhard Zimmermann and Jan Peter Schmidt